Determınants Of Tax Avoıdance - Dewa Putu Yogi Dananjaya; Wahidatul Husnaini (Cita Konsultindo Research Center, 2024)
This study aims to test empirically the determinants of tax avoidance. The research sample was collected from companies on the Indonesian Stock Exchange from 2020 to 2022. Based on purposive sampling, 683 companies were observed. The hypotheses were tested using multiple linear regression with Stata 14 software. The study results indicate that capital intensity negatively impacts tax avoidance, profitability positively affects tax avoidance, and company size does not.